Long-term monitoring in the boreal forest reveals high spatio-temporal variability among primary ecosystem constituents - Krebs, Charles J.; Boutin, Stan; Boonstra, Rudy; Murray, Dennis L.; Jung, Thomas S.; O’Donoghue, Mark; Gilbert, B. Scott; Kukka, Piia M.; Taylor, Shawn D.; Morgan, T.; Drummond, Ryan; Sinclair, Anthony R. E.; et al. (Frontiers in Ecology and Evolution, 2023)
To determine how the boreal forest ecosystem will respond to climate we have monitored white spruce cone crops, ground berry production, above-ground mushroom abundance, and the abundance of small mammals, snowshoe hares, and carnivores across 5 sites in the Yukon, Canada. Monitoring began in 1973 at Lhù'ààn Mânʼ (Kluane Lake) and additional protocols were added until a complete sequence was fixed in 2005 at all 5 sites and continued until 2022. White spruce cone counts show mast years at 3-7-year intervals. Ground berries and soapberry counts were highly variable among sites and counts of berries did not correlate among sites or between years for different species. Red-backed voles showed clear 3-4-year cycles at Kluane and probably at the Mayo and Watson Lake but showed only annual cycles in Whitehorse and Faro.Snowshoe hares fluctuated in 9-10-year cycles in a travelling wave, peaking one year earlier at Watson Lake but in synchrony at all other sites with no obvious sign of peak density changing over the last 50 years at Kluane Lake. Red squirrel numbers at Kluane exhibit markedly inter-year variability, driven mainly by episodic white spruce cone crops and predation from Canada lynx and coyotes as the hare cycle collapses. Snow track counts to index mammalian predators have been conducted our Kluane and Mayo sites, indicating that lynx numbers rise and fall with a 1-2-year lag at these two sites in a travelling wave tracking the hare cycle. Coyotes and lynx at Kluane peak together following the hare cycle, but coyote counts are also depressed during deep snow years.We are continuing to monitor wildlife abundance, cone crops, berry production, and mushroom biomass to measure changes associated with increasing temperature and fluctuating rainfall. The Yukon boreal forest is changing as climate shifts, but the changes are slow, variable across sites, taxa specific, and of uncertain predictability.